Jewish Anti-Christian Polemical Treatises in Early Modern Central and Eastern Europe: Where are They? - Daniel J. Lasker (Wrocławski Przegląd Teologiczny, 2018)
Jewish anti-Christian polemical treatises comprise a well-known genre in medieval Jewish literature. It is generally thought that these books were written in response to Christian missionary pressure. Yet, when considering Central and Eastern Europe in the early modern period, one sees that this genre is almost nonexistent, despite continuing Christian attempts at converting Jews. An analysis of medieval Jewish anti-Christian writings shows that rather than being necessarily a response to Christian missionary pressure, many of them are part of the larger Jewish theological enterprise. Hence, such works are prevalent in areas where Jews engaged in theology – the Islamic world, Iberia, Provence, and Italy – and almost nonexistent in northern Europe (Ashkenaz), where there was little interest in theology. This pattern continued into the early modern period, at which time Ashkenazic Jews still produced almost no anti-Christian polemical works. The most important early modern, Central and Eastern European anti-Christian book, the very popular Faith Strengthened, was written by a Lithuanian Karaite Isaac of Troki (died 1594), reinforcing our knowledge that Central and Eastern European Karaite Jews did not share the Ashkenazi intellectual ethos of their Rabbanite neighbors.